A survey of security and smart home automation based on internet of things technology - Sarah Mohammed Shareef; Zainab Adnan Abbas; Zahraa Mohammed Hilal (Indonesian Journal of Electrical Engineering and Computer Science, 2022)
The internet of things (IoT) refers to the physical tools that are embedded with Internet, software, electronics, sensors and network connectivity. This involves many different systems, for example, healthcare, smart home and so on. The security problem of the Internet of Things and the Smart Home infrastructure is considered, which has become an urgent issue due to the high popularity, low systemic research and the growth of threats to "us" (people seeking comfort) from "them" (surrounding things, which becoming increasingly intelligent, automated). The research is based both on a systemic, infrastructure understanding, and on an architectural, problem-oriented level. Key security risks for the infrastructure of various types-software and technical, technological, socio-psychological and others-were analyzed. The evolutionary problems of the internet of things and factors influencing the vulnerability of infrastructures have been investigated. In addition to traditional network security tasks, specific tasks (direct and reverse, for identification) are highlighted in IoT interactions and environments. This paper provides an overview of the related work in IoT, together with the open challenges and future research directions using Arduino platform (such as "thick server-thin client") to simulation modeling of time delay probability distribution based on identified simple model.